2022
DOI: 10.3892/ijo.2022.5402
|View full text |Cite
|
Sign up to set email alerts
|

HHLA2 promotes tumor progression by long non‑coding RNA H19 in human gallbladder cancer

Abstract: Advanced gallbladder cancer (GBC) is one of the most malignant of all types of biliary tract cancers that is associated with poor prognosis and high mortality. Accumulating evidence suggest that the B7 family of proteins serve an essential role in various types of cancers, including GBC. However, the potential function and regulatory mechanism of human endogenous retrovirus-H long terminal repeat-associating protein 2 (HHLA2; also known as B7-H7 or B7H5) in GBC remain poorly understood. In the present study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Expression of EMT markers, such as E-cadherin, N-cadherin, and Vimentin, were significantly changed after the knockdown of HHLA2 expression in human ccRCC [ 27 ]. Zhang et al found out that HHLA2 via an impact on EMT in advanced gallbladder cancer can promote tumor progression [ 28 ]. They presented the hypothesis that HHLA2 may be involved in the Wnt/βcatenin axis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of EMT markers, such as E-cadherin, N-cadherin, and Vimentin, were significantly changed after the knockdown of HHLA2 expression in human ccRCC [ 27 ]. Zhang et al found out that HHLA2 via an impact on EMT in advanced gallbladder cancer can promote tumor progression [ 28 ]. They presented the hypothesis that HHLA2 may be involved in the Wnt/βcatenin axis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that HHLA2 could play a significant role in gallbladder cancer (GBC) as well. Zhang et al found that among 89 examined patients, all cases exhibited HHLA2 staining [36]. In another study, high HHLA2 expression was observed in 53.68% of samples in the training group and 60.19% of cases in the testing group.…”
Section: Hhla2 In Gallbladder Cancermentioning
confidence: 93%
“…Notably, according to other authors, higher Nevin and TNM stages were associated with the high expression of HHLA2, B7-H3, and B7-H4 in both the training and testing groups. Elevated HHLA2 expression was also correlated with a lower density of CD8+ TILs in the training group (p = 0.001), but there was no relationship between HHLA2 expression and Foxp3 + TILs [36,37].…”
Section: Hhla2 In Gallbladder Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…[173][174][175][176] In in vivo experiments of human gallbladder cancer, the HHLA2 overexpression promoted tumor progression while its knockdown reduced the sizes of the GBC tumors. 177 Conversely, the HHLA2 ablation inhibited both TGF-β1-and long noncoding RNA H19-induced GBC progression in vitro. However, in a recent study on human ccRCC that evaluated the HHLA2 prognostic value, a positive correlation between increased HHLA2 and survival rates is reported.…”
Section: New B7 Family Checkpoints Moleculesmentioning
confidence: 98%